Pembelajaran dengan Metode Kisah (storytelling): Ekstensi dan Intensi Metode Linguistik dalam Bahasa Al Qur’an dengan Bentuk Imperatif - Siswati, Via Linda (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Long before writing, the only culture was oral and oral culture. Storytelling means participating, and helping children participate, in one of the most ancient human habits. The meaning we can draw from Gabriel's hadith as a way to understand the world of 'religious meaning' and be reminded that formal learning remains significant but that, interestingly, the Qur'an does not mention these activities while imperatively declaring